GRAMMATICAL EQUIVALENCE IN THE INDONESIAN TRANSLATION OF GALBRAITH’S THE CUCKOO’S CALLING - Alfonsa Vina Kanasya; Barli Bram (Linguistik Indonesia, 2023)
The aim of this paper is to analyze the grammatical equivalence in the Indonesian translation of Robert Galbraith’s novel, The Cuckoo’s Calling. The translated version is titled Dekut Burung Kukuk, translated by Siska Yuanita. The theory used in this research is the translation theory by Baker (2018) where five grammatical categories were analyzed, namely, number, gender, person, tense and aspect, and voice. This is a qualitative study as it was conducted by analyzing the text of the books and comparing the source and target language. The results show that the Indonesian translation of ‘The Cuckoo’s Calling’ was mostly grammatically equivalent, meaning that all five grammatical categories appeared in the Indonesian version and were well adjusted. Some necessary changes were made due to the different natures of both languages and to improve the translation quality and clarity.